Alat Feeding Ayam Otomatis Berbasis Arduino - Tesar Kornelius; Mohammad Dahlan; Noor Yulita Dwi Setyaningsih (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2024)
The increasing population in Indonesia has resulted in increased food needs. One of the factors that affects chicken production is the management of the feeding system. The purpose of this study is to design and create an automatic chicken feeder based on Arduino. Calibrate the Load Cell Sensor. Control the AC motor as a metal screw driver for feeding with a load cell sensor. Determine the amount of chicken feed according to the specified setting point and Connect the MCU Node to the telegram. This study uses the "Research and development" research method. Consisting of literature studies, hardware design, software design, tool design, and data collection, analysis and conclusions. Overall testing was carried out for 2 days starting from 6 am to 4 pm. The capacity of the tank is filled with 3 kg of feed. The setting point for feeding in the morning is 200 grams while in the afternoon it is 300 grams, for feed output there are 2 containers. Testing on the first day at 7 am the weight of the feed coming out of container 1 was 221 grams while in container 2 it was 225 grams, for 4 pm the weight of the feed coming out of container 1 was 352 grams while in container 2 it was 357 grams. Testing on the second day at 7 am the weight of the feed coming out of container 1 was 219 grams while in container 2 it was 221 grams, for 4 pm the weight of the feed coming out of container 1 was 346 grams while in container 2 it was 348 grams. Telegram notification sends a message when the amount of feed remaining is 1405 grams. The results of the weight of the feed coming out are different from the specified setting point value, the amount of feed coming out exceeds the setting point value. This is because the output hole of the feed that comes out through the PVC pipe is too large. An "automatic chicken feed tool based on Arduino" has been successfully created, the tool created is equipped with a load cell sensor that facilitates the process of feeding chickens. Making a system for pouring feed into the hopper automatically by making a conveyor so that it does not need to be done manually. Making automatic chicken feed based on Arduino on a large scale so that it can cover a larger number. Addition of making automatic drinking places on automatic chicken feed based on Arduino.